Intercentre variance in patient reported outcomes is lower than objective rheumatoid arthritis activity measures: a cross-sectional study - (:unkn) unknown (OXFORD UNIV PRESS, 2017)
Objective. To assess intercentre variability in the ACR core set measures, DAS28 based on three variables (DAS28v3) and Routine Assessment of Patient Index Data 3 in a multinational study. Methods. Seven thousand and twenty-three patients were recruited (84 centres; 30 countries) using a standard protocol in the Quantitative Standard Monitoring of Patients with RA study. Analysis of variance (ANOVA) and mixed-effect analysis of covariance models were used to model the relationship between study centre and different patient-reported and physician-reported RA activity measures. These models were built to adjust for the remaining ACR core set measure (for each ACR core set measure or each composite index), socio-demographics and medical characteristics. ANOVA and analysis of covariance models yielded similar results, and ANOVA tables were used to present variance attributable to recruiting centre. Results. The proportion of variances attributable to recruiting centre was lower for patient reported outcomes (PROs: pain, HAQ, patient global) compared with objective measures (joint counts, ESR, physician global) in all models. In the full model, variance in PROs attributable to recruiting centre ranged from 1.53% for patient global to 3.71% for HAQ compared with objective measures that ranged from 5.92% for physician global to 9.25% for ESR; and was lower for Routine Assessment of Patient Index Data 3 (2.6%) compared with DAS28v3 (11.75%). Conclusion. Intercentre variability in PROs is lower than objective measures of RA activity demonstrating that PROs may be more comparable across centres, and the need for standardization of objective measures.
Keywords: rheumatoid arthritis; disease activity assessment; patient reported outcomes; intercentre variance; DISEASE-ACTIVITY MEASURES; TRIALS; MULTICENTER; RELIABILITY; PHYSICIANS; CLUSTER; COUNTS; HEALTH; SCORES; CARE